Widespread myeloid sarcoma with KMT2A rearrangement involving the testis, oral cavity, heart, kidney and gallbladder without bone marrow involvement. (2022) - Kapur, Rohan; Steinberg, Amir; Moussly, Sammy; Trias, Juan Andres; Quintas, Joseph
Abstract: Myeloid sarcoma is a solid hematological tumor consisting of growing immature myeloid cells in tissues outside the bone marrow. Myeloid sarcoma presenting before the onset of bone marrow disease is rare. Here, we report the case of a young 35-year-old male who presented with testicular mass and was diagnosed with widespread myeloid sarcoma involving internal organs like heart, kidney and gallbladder. Peripheral blood and bone marrow examination did not show any evidence of leukemia. Genetic analysis was significant for KRAS G12D mutation and KMT2A rearrangement. Induction chemotherapy for extramedullary AML with cladribine, cytarabine, GM-CSF and idarubicin (CLAG-IDA) achieved complete remission. However, the patient relapsed after 2 months and developed rapidly progressive disease. The disseminated nature of the disease in a patient without bone marrow involvement are what make this case extremely rare. Involvement of organs like heart, gall bladder and kidney is also uncommon. Isolated myeloid sarcoma is a challenge to diagnose as there are no manifestations of leukemia in peripheral blood or bone marrow, so it is usually not considered among the differential diagnoses. KM2TA rearrangement identified on genetic analysis is a rare finding in patients with AML and is associated with poor outcomes. KRAS mutations are currently being studied as therapeutic targets in these patients. This case report describes the detailed diagnostic process and discusses the possible strategies for diagnosis and treatment that can be used in similar cases.